Effects of Prematurity on the Cutaneous Microcirculatory Network in the First Weeks of Life - Puchwein-Schwepcke, Alexandra; Grzybowski, Ann-Kristin; Genzel-Boroviczény, Orsolya; Nussbaum, Claudia (Frontiers in Pediatrics, 2019)
Preterm infants are at increased risk for hypertension in adolescence. Microcirculatory dysfunction has been identified as an underlying cause for cardiovascular disease. Our goal was to document the development of the cutaneous microcirculation in preterm infants during the first weeks of life and to compare it to the situation in term infants at birth. In 20 preterm infants, microcirculatory parameters were obtained prospectively by Sidestream Dark Field Imaging at the upper inner arm once a week until discharge or 37 weeks of gestational age. A single microcirculatory measurement was obtained in 30 term infants during the first three days of life. Videos were blinded and analyzed with the AVA software. Microcirculatory parameters in preterm infants differ significantly from term infants with a lower vessel surface (VS), a lower percentage of large and medium but higher percentage of small vessels, a higher Functional Vessel Density (FVD) and a higher Microcirculatory Flow Index (MFI). In multivariable linear regression models we could demonstrate a statistically significant association between the dependent microcirculatory variables (VS, diameter distribution, MFI) and gestational age as independent predictor variable while adjusting for postnatal days of life. Looking at the longitudinal follow-up data of preterm infants by means of a multivariable mixed-effects linear regression model adjusting for clinical variables, there is a significant decrease in FVD with increasing postnatal age, however no other significant changes in microcirculatory parameters over time. Accordingly, comparing the microcirculatory parameters of near term former preterm infants with term born neonates, we could still find significant differences with a higher FVD, lower VS and differences in vessel diameters in the former premature group. Infants born prematurely exhibit distinct microcirculatory alterations compared to term neonates with gestational age at birth being associated with microvascular parameters. Interestingly, this premature vascular phenotype persists even close to corrected term age. In view of the known increased cardiovascular risk of former preterm infants, our observations might have important clinical impact. The factors governing the development of the microvascular network in preterm infants and the contribution of microcirculatory changes observed here to vascular pathology in later life need to be further investigated.